Functional training - Santana, Juan Carlos 1959- (Human Kinetics, 2016)
This revolutionary approach to training and conditioning methods will improve function in any sport or activity. Offering strength, endurance, power and sport-specific exercises and programming, Functional Training is a comprehensive resource for every athlete, coach and athletic trainer